Almost paradise. Season 1 [videorecording (DVD)] - Devlin, Dean; Rosen, Gary (Electric Entertainment, 2020)
When life-threatening hypertension forces US DEA agent Alex Walker into early retirement, he decides to move to a tranquil deserted beach he remembered visiting in the Philippines many years ago. But when he arrives, he discovers that, in the interim, dozens of luxury resorts have been built, filling this once secluded island with jet skis, honeymooners, screaming children...and the rich and famous criminals of the world. Against doctor's orders, Alex finds himself drawn into cases where he uses his skills as a longtime operative to put away the bad guys that cross his path.